BACKGROUND VARIABLES AND PREVAILENCE OF BULLYING AMONG SECONDARY SCHOOL STUDENTS IN BAYELSA STATE, NIGERIA - Uche, Rachel D.; Ngwu, Maria E. (IJRDO- Journal of Educational Research, 2016)
This study investigated the extent to which background variables contribute towardsprevalence of bullying among secondary school students in Bayelsa State, Nigeria. Threehypotheses were formulated and using a combination of stratified and simple randomsampling techniques, 640 secondary school students were selected from ten schools in five outof the eight local government areas (LGAs) of the state. The ex-post facto design wasemployed and data was collected using a questionnaire titled, Student Bullying Index (SBI).Accruing data was analyzed using Independent t-test and the result indicated significantdifferences in bullying among students on the bases of school location, parental socioeconomicstatus (SES) and family type. The conclusion is that there is a high incidence ofbullying in the area under study and because bullying has the capacity to place unnecessarystrain and stress on students, parents and the educational system, if left unchecked, thefollowing action plan is recommended for school guidance counsellors: Advocacy for goodgovernance; for small sized classes and for improved infrastructure and school facilities, inorder to keep students maximally engaged.